Clinical risk factors for acute ischaemic and haemorrhagic stroke in patients with infective endocarditis. Issue 9 (4th September 2018) - Valenzuela, Ives; Hunter, Madeleine D.; Sundheim, Kathryn; Klein, Bradley; Dunn, Lauren; Sorabella, Robert; Han, Sang M.; Willey, Joshua; George, Isaac; Gutierrez, Jose
Abstract: Background: Stroke as a complication of infective endocarditis portends a poor prognosis, yet risk factors for stroke subtypes have not been well defined. Aim: To identify risk factors associated with ischaemic and haemorrhagic strokes. Methods: A retrospective patient chart review was performed at a single US academic centre to identify risk factors and imaging for patients who were 18 years or older with infectious endocarditis (IE) and stroke diagnoses. Differences in patient characteristics by stroke status were assessed using univariate analysis, χ 2 or student's t ‐test as well as logistic regression models for multivariable analyses and correlation matrices to identify possible collinearity between variables and to obtain odds ratios (OR) and their 95% confidence intervals. Results: A final sample of 1157 participants was used for this analysis. The total number of non‐surgical strokes was 178, with a prevalence of 15.4% (78% ischaemic, 10% parenchymal haemorrhages, 8% subarachnoid haemorrhages and 4% mixed ischaemic/haemorrhagic). Multivariate risk factors for ischaemic stroke included prior stroke (OR 2.0, 1.3–3.1), Staphylococcus infection (OR 2.0, 1.3–3.0), mitral vegetations (OR 2.2, 1.4–3.3) and valvular abscess (OR 2.7, 1.7–4.3). Risk factors for haemorrhagic stroke included fungal infection (OR 6.4, 1.2–34.0), male gender (OR 3.5, 1.4–8.3) and rheumatic heart disease (OR 3.3, 1.1–10.4). Conclusion: Among patients with IE, there exist characteristics that relate differentially to ischaemic and haemorrhagic stroke risk.